Low hemoglobin and venous saturation levels are associated with poor neurological outcomes after cardiac arrest. (August 2020) - Zama Cavicchi, Federica; Iesu, Enrica; Franchi, Federico; Nobile, Leda; Annoni, Filippo; Vincent, Jean-Louis; Scolletta, Sabino; Creteur, Jacques; Taccone, Fabio Silvio
Abstract: Introduction: Hemoglobin (Hb) is a main determinant of tissue oxygen delivery and anemia could be particularly harmful in post-anoxic brain injury. The aim of this study was to evaluate the association of Hb and venous Hb oxygen saturation (SvO2 /ScvO2 ) with long-term neurological outcome in patients admitted after cardiac arrest (CA). Methods: Analysis of adult CA patients admitted to the Department of Intensive Care of the Erasme University Hospital (Brussels, Belgium) over 9 years. We retrieved all data concerning CA characteristics as well as Hb during the first 48 h since injury as well as the need for red blood cells transfusions (RBCT). Minimum Hb and Hb oxygen saturation values were recorded. Neurological outcome was evaluated 3 months after CA. Unfavorable neurological outcome (UO) was defined as a Cerebral Performance Categories (CPC) score of 3–5. Results: We treated 414 patients patients with CA, including 231 (56%) out-of-hospital cardiac arrest (OHCA) and 158 (38%) with an initial shockable rhythm. Median Hb concentration on admission was 12.0 [9.9−13.7] g/dL and the lowest Hb concentration was 10.0 [8.1−11.0] g/dL; 127 patients (31%) received at least one RBCT. Hb oxygen saturation on admission was 67 [59−74]%, while the lowest value was 60 [53−68]%. Low Hb and Hb oxygen saturation values were independently associated with UO; the optimal cut-off to predict UO was <9.9 g/dL and <60%, respectively. Conclusions: Low hemoglobin values and low values of oxygen venous saturation are significantly associated with unfavorable neurological outcome in adult patients resuscitated from cardiac arrest.